2015 IEEE/ACM 12th Working Conference on Mining Software Repositories 2015
DOI: 10.1109/msr.2015.37
|View full text |Cite
|
Sign up to set email alerts
|

A Method to Detect License Inconsistencies in Large-Scale Open Source Projects

Abstract: The reuse of free and open source software (FOSS) components is becoming more and more popular. They usually contain one or more software licenses describing the requirements and conditions which should be followed when been reused. Licenses are usually written in the header of source code files as program comments. Removing or modifying the license header by re-distributors will result in the inconsistency of license with its ancestor, and may potentially cause license infringement. But to the best of our kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…They investigated the extent to which terms of the licenses were adhered during the cloning of these code fragments. Similarly, Wu et al [31] found that cloned files have a potential to be inconsistent in terms of licenses (e.g., one has a license, while the other does not). The paper describes the types of inconsistencies and illustrates the problem and the difficulty to resolve it through an empirical study of Debian 7.5.…”
Section: B Empirical Studies On Licenses Adoption and Evolutionmentioning
confidence: 97%
“…They investigated the extent to which terms of the licenses were adhered during the cloning of these code fragments. Similarly, Wu et al [31] found that cloned files have a potential to be inconsistent in terms of licenses (e.g., one has a license, while the other does not). The paper describes the types of inconsistencies and illustrates the problem and the difficulty to resolve it through an empirical study of Debian 7.5.…”
Section: B Empirical Studies On Licenses Adoption and Evolutionmentioning
confidence: 97%
“…Vendome et al [10] studied on common understandings among developers on the reason and timing for changing a license, through interviews of developers. Wu et al [11] proposed a method to detect license inconsistencies in a large-scale OSS. As a result of an experiment using Debian v7.8.0, license inconsistencies were detected for Debian v7.8.0.…”
Section: License Compliancementioning
confidence: 99%
“…To explore empirically this hypothesis, based on what has been done in previous research [8,12,21,22], this study focuses on four types of legal restrictions that may be applied to the free and open source code. The first relates to whether the source code is "restrictive", requiring derivative works to be released under the same license in case of redistribution [19]; the second, to whether it is "highly restrictive", which besides being restrictive, forbids the source code to be even mingled for compilation with software of a different license [19]; the third, to whether the code may be relicensed, meaning that "any distributor has the right to grant a license to the software […] directly to third parties" ( [7], p. 88); and the fourth, to whether a project is licensed under the Academic Free License, since it was written to correct problems of important licenses such as MIT and BSD [7] and is understudied.…”
Section: The Choice Of License and Fsp Successmentioning
confidence: 99%